2013
DOI: 10.1139/cjm-2013-0168
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Pseudomonas aeruginosa in predominant biofilm or planktonic forms of existence in mixed culture with Escherichia coli in vitro

Abstract: Pseudomonas aeruginosa and Escherichia coli are known to be involved in mixed communities in diverse niches. In this study we examined the influence of the predominant form of cell existence of and the exometabolite production by P. aeruginosa strains on interspecies interactions, in vitro. Bacterial numbers of P. aeruginosa and E. coli in mixed plankton cultures and biofilms compared with their numbers in single plankton cultures and biofilms changed in a different way, but were in accordance with the form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
1
22
1
Order By: Relevance
“…A higher growth rate and stronger adhesive properties of 1 species can cause it to outgrow other populations (Cerqueira and others ). Several other studies reveal that the formation of antimicrobial, exometabolite (Kuznetsova and others ), and bacteriocin (Tait and Sutherland ) producers may have a fitness advantage over other nonproducer populations in mixed‐species biofilms. A well‐defined microscale spatial structure of mixed‐species biofilms and a minimal distance between each species separated by the EPS components could act as “public goods” and barriers to stabilize the mixed‐species biofilms (Kim and others ).…”
Section: Paradox Of Fitness Of Different Populations In Mixed‐speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher growth rate and stronger adhesive properties of 1 species can cause it to outgrow other populations (Cerqueira and others ). Several other studies reveal that the formation of antimicrobial, exometabolite (Kuznetsova and others ), and bacteriocin (Tait and Sutherland ) producers may have a fitness advantage over other nonproducer populations in mixed‐species biofilms. A well‐defined microscale spatial structure of mixed‐species biofilms and a minimal distance between each species separated by the EPS components could act as “public goods” and barriers to stabilize the mixed‐species biofilms (Kim and others ).…”
Section: Paradox Of Fitness Of Different Populations In Mixed‐speciesmentioning
confidence: 99%
“…The combined effect would be the final goal for the selection of species from mixed‐species biofilms in food niches. Competitive interactions might regulate biofilms dispersal and the outcome for 1 species from among the population from mixed‐species biofilms or reduce the population size (Esteves and others ; Almeida and others ; Giaouris and others ; Kuznetsova and others ). A higher growth rate and stronger adhesive properties of 1 species can cause it to outgrow other populations (Cerqueira and others ).…”
Section: Paradox Of Fitness Of Different Populations In Mixed‐speciesmentioning
confidence: 99%
“…E. coli has been demonstrated to outgrow P. aeruginosa in biofilm cultures but outgrown in planktonic batch cultures (Culotti and Packman, 2014). Kuznetsova et al, (2013) also demonstrated using E. coli K12 TG1, a reference P. aeruginosa strain (ATCC 27853) and clinical P. aeruginosa strains (BALG and 9-3) that the CFU of E. coli in mixed culture with P. aeruginosa 27853 and 9-3 were significantly above that of the pure culture but that with P. aeruginosa BALG did not show any difference after 12 h of incubation. For the CFU of P. aeruginosa, different effects were observed for the different strains in mixed culture; the CFU of P. aeruginosa BALG was significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been determined that horizontal gene transfer occurs between these species; for example, catabolic pathways for metabolism of phenylacetic and p ‐hydroxyphenylacetic are shared by E. coli and P. putida ; and it has also been shown that the Pseudomonas TOL plasmid can be transferred to E. coli (Nakazawa and Yokota, ; Bradley and Williams, ; Ramos‐González et al ., ; Ramos‐González et al ., ). However, to date, interactions between E. coli and Pseudomonas strains that are capable of co‐existing have been only partially defined (Kuznetsova et al ., ; Culotti and Packman, ). This study was conceived as a proof‐of‐concept to study intermicrobial relationships between environmental microbes; specifically, their ability to communicate, activate mechanisms of defense, or elicit critical metabolic changes required for survival in certain environments.…”
Section: Introductionmentioning
confidence: 99%